Pencegahan Perundungan pada Peserta Didik Melalui Elemen Berkebhinekaan Global Profil Pelajar Pancasila - Giantomi Muhammad; Haditsa Qur’ani Nurhakim; Muhammad Rifaldi; M. Imam Pamungkas (At Turots: Jurnal Pendidikan Islam, 2024)
Bullying continues to occur every year and always increases rapidly. It's time for all components of society, especially schools, to think about follow-up actions and solutions. Bullying cannot be tolerated because it can change and damage the civilization that is being developed through the younger generation. They are the ones who will inherit the next civilization in the future. The Global Diversity Element is a breakthrough in the Pancasila Student Profile program. These elements unite diversity as an effort to mutual respect, respect and tolerance. This research uses a qualitative approach and literature study methods. The results obtained strive to implement elements of Global Diversity through teaching, coaching, supervision, motivation and enforcement of rules.